Analysis and design of controllers vectorial PI, optimal LQR, H-infinite for a system of magnetic suspension (2006)
This paper presents the modeling analysis and design of robust controllers applied to magnetic suspension system . First, from the nonlinear model and linearizing the system around a operation point obtains the nominal model; the specifications of performance settle down required to obtain the sef of models of bounded uncertainties. "Design controllers (PI Vectorial, LQR, Hinf). The different controllers compared and evaluated.